2009
DOI: 10.1521/jscp.2009.28.3.307
|View full text |Cite
|
Sign up to set email alerts
|

Does a Lack of Life Meaning Cause Boredom? Results from Psychometric, Longitudinal, and Experimental Analyses

Abstract: existential theory and previous qualitative research have suggested that a lack of life meaning and purpose causes boredom, as well as other types of negative affect such as depression or anxiety. although these variables have been shown to be correlated at one point in time, the relationships among these constructs have not been investigated using a controlled, quantitative research design. in Study 1a (N = 131), boredom was shown to be related to, yet psychometrically distinct from, life meaning, depression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 57 publications
8
149
1
1
Order By: Relevance
“…Items relating to sadness, anger, and frustration were taken from Roseman and colleagues 2 and we generated items for boredom based on literature. Specifically, research suggests that boredom relates to a lack of challenge (e.g., Csikszentmihalyi, 2000), a lack of purpose or meaning (e.g., Barbalet, 1999;Fahlman et al, 2009), and a subsequent desire for changing aspects of the situation or to pursue challenge and meaning in subsequent behavior (e.g., Csikszentmihalyi, 2000;Smith et al, 2009). We focused especially on these domains of the proposed boredom experience because they seemed to be central to the boredom experience and may have a particularly pronounced impact on subsequent behavior (e.g., Sansone, 1992;Rupp & Vodanovich, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Items relating to sadness, anger, and frustration were taken from Roseman and colleagues 2 and we generated items for boredom based on literature. Specifically, research suggests that boredom relates to a lack of challenge (e.g., Csikszentmihalyi, 2000), a lack of purpose or meaning (e.g., Barbalet, 1999;Fahlman et al, 2009), and a subsequent desire for changing aspects of the situation or to pursue challenge and meaning in subsequent behavior (e.g., Csikszentmihalyi, 2000;Smith et al, 2009). We focused especially on these domains of the proposed boredom experience because they seemed to be central to the boredom experience and may have a particularly pronounced impact on subsequent behavior (e.g., Sansone, 1992;Rupp & Vodanovich, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…For example, some of the research on boredom proneness indicates that it is associated with a greater likelihood to suffer from severe social and psychological dysfunctions, such as eating disorders and pathological gambling (e.g., Blaszczynski et al, 1990). Other findings suggest that boredom proneness correlates with a string of negative emotions, such as depression, fear, anxiety, loneliness, and hopelessness (e.g., Fahlman, Mercer, Gaskovski, Eastwood, & Eastwood, 2009). …”
Section: Boredom: the Absence Of Meaningmentioning
confidence: 99%
“…Studies in this category have been consistently conducted across all three decades searched, with the majority being empirical (62%). Self-report measures were typically utilized to assess state boredom, and such research has suggested that state boredom is conceptually distinct from feelings of depression, anxiety, frustration, and perceptions of life meaning (Fahlman et al 2009). In fact, recent work on sequences of emotions has suggested that frustration can either be an antecedent or a consequence of boredom D'Mello et al 2007).…”
Section: Contemporary Definitions Of Boredommentioning
confidence: 99%